2020
DOI: 10.1038/s42003-020-01148-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of animal-derived tigecycline-resistant Escherichia coli across China reveals recent endemic plasmid-encoded tet(X4) gene

Abstract: Public health interventions to control the recent emergence of plasmid-mediated tigecycline resistance genes rely on a comprehensive understanding of its epidemiology and distribution over a wide range of geographical scales. Here we analysed an Escherichia coli collection isolated from pigs and chickens in China in 2018, and ascertained that the tet(X4) gene was not present at high prevalence across China, but was highly endemic in northwestern China. Genomic analysis of tet(X4)-positive E. coli demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 27 publications
6
53
1
Order By: Relevance
“…The presence of these plasmids makes the dissemination of bla NDM−1 and/or mcr more heterogeneous. It was worth note that the elements mediating the spread of high-level TGC resistance gene tetX4 in E. coli isolates from pig farms in this study shared highly homologous to those reported previously 3,17,31 (Fig. 6D), suggesting the dissemination of tetX4 might be not as heterogeneous as bla NDM and mcr.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The presence of these plasmids makes the dissemination of bla NDM−1 and/or mcr more heterogeneous. It was worth note that the elements mediating the spread of high-level TGC resistance gene tetX4 in E. coli isolates from pig farms in this study shared highly homologous to those reported previously 3,17,31 (Fig. 6D), suggesting the dissemination of tetX4 might be not as heterogeneous as bla NDM and mcr.…”
Section: Discussionsupporting
confidence: 74%
“…To determine the genetic propensity of the MDR/XDR-E. coli isolates to spread into the human sector, the genetic relatedness of the 515 MDR/XDR-E. coli isolates from pig farms in China to 287 publicly available draft genomes of human commensal E. coli (Bioproject no. PRJNA4001047) were investigated 17 . The 802 E. coli isolates were phylogenetically divided into three lineages (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Tet(X/X2) exhibited a wide host range and was present in a variety of bacteria, including Bacteroides spp., Delftia spp., Enterobacteriaceae , Riemerella anatipestifer , Parabacteroides spp., etc., while Tet(X4) was occasionally detected in Aeromonas caviae and Acinetobacter spp. ( 17 , 18 ) but mainly found in E. coli ( 9 , 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…All of these 32 tet(X)-positive strains were subsequently identified as E. coli by 16S rRNA sequencing. Several papers have reported the discovery of tet(X4)-carrying E. coli [ [37][38][39], illustrating the fact that E. coli is an important carrier and indicator organism for the spread of tet(X4). Remarkably, two different strains carrying tet(X4) were isolated from each sample among three samples (Table S2), indicating that the tet(X4) gene could spread in the same microbiota.…”
Section: Recognition and Characterization Of Tet(x)-positive Enterobacteralesmentioning
confidence: 99%